The Effect of a Period of Corrective Exercises on Balance and Performance of Female Volleyball Players with Knee Dynamic Valgus Defect - Ebrahim Mohammad Ali Nasab Firouzjah; Rogayeh Imani (Shiraz University of Medical Sciences, 2023)
Background: This study aimed to assess the impact of a corrective exercise program on the balance and performance of female volleyball players with knee dynamic valgus defects. Methods: This study employed a semi-experimental design conducted in the field. the study's target population comprised female volleyball players in East Azarbaijan with knee dynamic valgus defects. From this population, 30 subjects were selected and randomly divided into control and experiment groups, following the completion of personal profiles and screening for knee dynamic valgus defects using a squat test. The study measured static and dynamic balance through the BESS (Balance Error Scoring System) and Y balance tests for lower limb assessment and upper extremity function through the Y functional test for upper extremities in both groups. The experimental group underwent a 10-session program of corrective exercises, while the control group continued with their regular volleyball exercises. After the training period, both groups underwent a post-test. The data's normality was assessed using the Shapiro-Wilk test. The effect of the corrective exercise program on the research's dependent variables was analyzed through covariance analysis and dependent t-tests, with a confidence level set at P ≤ 0.05. Top of Form Results: The results showed a positive impact of corrective exercises on static and dynamic balance (P = 0.001) and upper extremity function (P = 0.001) in volleyball players with dynamic knee valgus defects. Conclusion: The study results demonstrate that the corrective exercise program, following the National Academy of Sports Medicine approach, significantly reduces knee dynamic valgus, improves balance, and enhances upper extremity function in young female volleyball players.